Host Genome–Metagenome Analyses Using Combinatorial Network Methods Reveal Key Metagenomic and Host Genetic Features for Methane Emission and Feed Efficiency in Cattle - Cardinale, Stefano; Kadarmideen, Haja N. (Frontiers in Genetics, 2022)
Rumen in cattle hosts numerous microbial communities that are involved in the digestive process, leading to notable amounts of methane emission, a significant contributor to global warming. In this study, our main objective is to reanalyze a publicly available dataset using our proprietary Synomics Insights platform that is based on novel combinatorial network and machine learning methods, to detect key metagenomic and host genetic features for methane emission and Residual Feed Intake (RFI) in dairy cattle. The Synomics Insights platform is based on combinatorial methods to detect features.. Focusing exclusively on enriched taxa, for methane emission the study identified 26 Order-level taxa that combinatorial networks reported as significantly enriched either in high or low emitters. Additionally, a Z-test on proportions found 81%of these taxa were differentially enriched between high and low emitters (P value < 0.05). In particular, the Phylum of Proteobacteria and the Order Desulfovibrionales was found enriched in high emitters, while the Order Veillonellales was found to be more abundant in low emitters. In comparison, using the publicly available tool ANCOM (Mandal et al., 2015) only the Order Methanosarcinales could be identified as differentially abundant between the two groups. We have also investigated a link between host genome and rumen microbiome by applying our platform to identify genetic determinants in cows that are associated with changes in heritable components of the rumen microbiome. Only 4 key SNPs were found by both our platform and GWAS, whereas the Synomics Insights platform identified 1,290 significant SNPs that were not found by GWAS. Gene Ontology (GO) analysis found Transcription Factor as the dominant biological function. We estimated heritability of a core 73 taxa from the original set of 150 core Order-level taxonomies and showed that some species are medium to highly heritable (0.25 to 0.62), paving the way for selective breeding of animals with desirable core microbiome characteristics. We identified a set of 113 key SNPs associated with >90% of these core heritable taxonomies. Finally, we have characterized a small set (<10) of SNPs strongly associated with key heritable bacterial Orders with known role in methanogenesis such as Desulfobacterales and Methanobacteriales.